2003
DOI: 10.1046/j.1439-0531.2003.00408.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cytokeratins in Bovine Sperm Outer Dense Fibre Fractions

Abstract: Outer dense fibres (ODF) are important substructures of mammalian sperm tails that are involved in the regulation of sperm motility. In this study, we investigated the identity of several sodium dodecyl sulphate (SDS)-insoluble ODF proteins. Bovine ODF were purified by separating sperm heads and tails using ultrasound and Percoll(R) density gradient centrifugation. Sperm flagella were treated with the detergent cetyltrimethylammonium bromide (CTAB). CTAB-insoluble material, which reportedly represents the ODF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 23 publications
(30 reference statements)
0
7
0
1
Order By: Relevance
“…Biochemical and immunological analyses have revealed that bovine ODF contain sperm keratins (31). Presently it is thought that the ODF mainly consists of cytoskeletal proteins and lacks membranes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical and immunological analyses have revealed that bovine ODF contain sperm keratins (31). Presently it is thought that the ODF mainly consists of cytoskeletal proteins and lacks membranes.…”
Section: Discussionmentioning
confidence: 99%
“…For the enrichment of ODF fractions, spermatozoa from about 50 ejaculates were used. ODF were purified by a previously published protocol (30,31) Purified bovine ODF were resuspended in SDS-sample buffer. The SDS-insoluble and -soluble proteins were separated by centrifugation for 15 min at 12,000 ϫ g. The supernatant was subjected to preparative SDS-PAGE.…”
Section: Preparation Of Outer Dense Fiber Proteins and Protein Sequenmentioning
confidence: 99%
“…Without using specific molecular probes, it is difficult to hypothesize which proteins compose the extraction-resistant cell remnant, but our electrophoretic result shows that they correspond to major protein bands in the profile of unextracted spermatozoa. Other authors have identified intermediate filament-like proteins in perinuclear theca (Kierszenbaum et al, 2003), outer dense fibres (Tres & Kierszenbaum, 1996;Hinsch et al, 2003) and fibrous sheath (Eddy et al, 1991;Jassim, 1991;Tres & Kierszenbaum, 1996;Catalano et al, 2001). In fact, the Odf proteins described as major constituents of outer dense fibres can be regarded as a group of keratins (Kierszenbaum, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Other authors have identified intermediate filament‐like proteins in perinuclear theca (Kierszenbaum et al. , 2003), outer dense fibres (Tres & Kierszenbaum, 1996; Hinsch et al. , 2003) and fibrous sheath (Eddy et al.…”
Section: Discussionmentioning
confidence: 99%
“…Keratin type II cytoskeletal 5 is present in the sperm flagellum (Calvin, ; Hinsch, Boehm, Groeger, Mueller‐Schoesser, & Hinsch, ) and contributes to its dense fibre composition (Lindemann & Kanous, 1),whose function is to maintain cell structure (Calvin, ; Hinsch et al, ).…”
Section: Discussionmentioning
confidence: 99%